No effect of prefrontal transcranial direct current stimulation (tDCS) on food craving, food reward and subjective appetite in females displaying mild-to-moderate binge-type behaviour - Jordan D. Beaumont; Michelle Dalton; Danielle Davis; Graham Finlayson; Alexander Nowicky; Mark Russell; Martin J. Barwood (Appetite, 2023)

Does sonification of action simulation training impact corticospinal excitability and audiomotor plasticity? - Fabio Castro; Ladan Osman; Giovanni Di Pino; Aleksandra Vuckovic; Alexander Nowicky; Daniel Bishop (Experimental Brain Research, 2021)
Sonification is a sensory augmentation strategy whereby a sound is associated with, and modulated by, movement. Evidence suggests that sonification could be a viable strategy to maximize learning and rehabilitation. Recent studies investigated sonification of action observation, reporting beneficial effects, especially in Parkinson’s disease. However, research on simulation training—a training regime based on action observation and motor imagery, in which actions are internally simulated, without physical execution—suggest that action observation alone is suboptimal, compared to the combined use of action observation and motor imagery. In this study, we explored the effects of sonified action observation and motor imagery on corticospinal excitability, as well as to evaluate the extent of practice-dependent plasticity induced by this training. Nineteen participants were recruited to complete a practice session based on combined and congruent action observation and motor imagery (AOMI) and physical imitation of the same action. Prior to the beginning, participants were randomly assigned to one of two groups, one group (nine participants) completed the practice block with sonified AOMI, while the other group (ten participants) completed the practice without extrinsic auditory information and served as control group. To investigate practice-induced plasticity, participants completed two auditory paired associative stimulation (aPAS) protocols, one completed after the practice block, and another one completed alone, without additional interventions, at least 7 days before the practice. After the practice block, both groups significantly increased their corticospinal excitability, but sonification did not exert additional benefits, compared to non-sonified conditions. In addition, aPAS significantly increased corticospinal excitability when completed alone, but when it was primed by a practice block, no modulatory effects on corticospinal excitability were found. It is possible that sonification of combined action observation and motor imagery may not be a useful strategy to improve corticospinal, but further studies are needed to explore its relationship with performance improvements. We also confirm the neuromodulatory effect of aPAS, but its interaction with audiomotor practice remain unclear.

Evaluation of the Numeric Rating Scale for perception of effort during isometric elbow flexion exercise - Sofia Lampropoulou; Alexander V. Nowicky (European Journal of Applied Physiology, 2012)